Development of active fish gelatin films with anthocyanins by compression molding. (November 2018) - Uranga, Jone; Etxabide, Alaitz; Guerrero, Pedro; de la Caba, Koro
Abstract: The efficient use of biomass is one of the overarching objectives within sustainable development. In this context, fish gelatin and anthocyanins derived from food processing waste were used to prepare bio-based films. Anthocyanins were extracted by a simple and sustainable process and characterized before analyzing their antioxidant activity as a function of pH, in order to select the film processing conditions. In this regard, it is worth mentioning that a more sustainable process than the conventional solution casting was used in the preparation of films, since compression molding is a more rapid and less energy-consuming process. Furthermore, anthocyanins incorporated into film forming formulations maintained their antioxidant activity, as shown by the radical scavenging capacity. Additionally, the incorporation of anthocyanins decreased the water sensitivity of films, maintaining mechanical properties and, thus, highlighting the potential of these films as active packaging. Graphical abstract: Image 1 Highlights: Anthocyanins were extracted from red cabbage by an environmentally friendly process. Bio-based films were processed by compression to reduce production time and costs. The incorporation of anthocyanins improved both water and mechanical resistance. Anthocyanin-incorporated films showed antioxidant activity.